2009
DOI: 10.1080/02701367.2009.10599561
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass and Circumference of Upper Arm Are Associated With Race Performance in Ultraendurance Runners in a Multistage Race—The Isarrun 2006

Abstract: In the present study, we investigated the association of anthropometric parameters with race performance in ultraendurance runners in a multistage ultraendurance run, in which athletes had to run 338 km within 5 consectitive days. In 17 male successful finishers, calculations of body mass, body height, skinfold thicknesses, extremity circumference, skeletal muscle mass (SM), and percentage body fat (%BF) were performed before the race to correlate anthropometric parameters with race performance. A positive ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
60
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 35 publications
5
60
4
1
Order By: Relevance
“…In our study all the Kenyan runners were distinguished by low BMI (19.55 ± 1.51), low body fat (5.41 ± 1.75%) and slim calves (37.84 ± 6.43 cm). similar results were published by Knechtle et al [19] and Kong et al [20]. In the chosen elite Kenyan runners they noticed low BMI (20.1 ± 1.8), low body fat (5.1 ± 1.6%) and slim legs (34.5 ± 2.3 cm), however in our study a negative correlation between the calf circumference and run time was found.…”
Section: Discussioncontrasting
confidence: 34%
“…In our study all the Kenyan runners were distinguished by low BMI (19.55 ± 1.51), low body fat (5.41 ± 1.75%) and slim calves (37.84 ± 6.43 cm). similar results were published by Knechtle et al [19] and Kong et al [20]. In the chosen elite Kenyan runners they noticed low BMI (20.1 ± 1.8), low body fat (5.1 ± 1.6%) and slim legs (34.5 ± 2.3 cm), however in our study a negative correlation between the calf circumference and run time was found.…”
Section: Discussioncontrasting
confidence: 34%
“…The association of anthropometric characteristics with overall race time was also investigated because in prior studies of ultra-endurance athletes, anthropometric variables such as a lower body mass (Knechtle, Duff, Welzel, & Kohler, 2009), a lower Body Mass Index (Hoffman, 2008), a lower body fat (Knechtle, et al, 2009d) and a lower upper arm circumference (Knechtle, Knechtle, Schulze, & Kohler, 2007;Knechtle, et al, 2009a) were related to faster race times, presumably due to great training and increased conditioning. In ultra-cyclists, a lower body fat was associated with a faster race time (Knechtle, et al, 2009d), but not skin-fold thicknesses (Knechtle & Rosemann, 2009;Knechtle, et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…Despite that the possible influence of body mass and other morphologic variables on physical performance has been the subject of previous investigations in both anaerobic 19,20 and aerobic 21,22 activities, as well as in the comparison between genders 23 , the results reached so far are still in-conclusive since the magnitude of the contribution of these variables seems to depend on the characteristics of the motor task required. In this study it was believed that the motor performance in each test could be largely explained by the morphological variables, which was not confirmed, mainly in relation to body mass, fat mass, and lean body mass in the FKPU test.…”
Section: Discussionmentioning
confidence: 84%